The use of Wonnolas in controlling gastrointestinal nematode infections in sheep under traditional grazing management in Indonesia - Beriajaya .; S.E. Estuningsih; Darmono .; M.R. Knox; D.R. Stoltz; A.J. Wilson (Indonesian Center for Animal Research and Development (ICARD), 1995)
Blocks containing 3% phenothiazine in solidified molasses (Wonnolas, Animeal Australia Ltd .) were tested to control gastrointestinal nematode infections and the effect on mineral status in sheep in villages in Cirebon, Indonesia. Two hundred and thirteen Javanese Thin Tail sheep which were grazed during the day and housed at night were divided into two groups on the basis of location . One group was allowed in an access to Wonnolas blocks when penned for 24 weeks while the other group remained untreated. The bodyweight was recorded and faecal samples were collected for egg counts and larval culture every four weeks. Sera and saliva samples were collected from 20 adult sheep in each group at weeks 0, 12 and 24 for mineral analysis by AAS and colorimetry. The results indicated that the mean egg counts of the treated group decreased from 576 epg to 123 epg and the percentage of sheep producing viable larvae decreased from 50% to 24%. In contrast egg counts of the control group increased from 768 epg to 4,840 epg and the percentage of sheep producing viable larvae increased from 65% to 84% over the same period . In the treated group the number of Haenronchus larvae declined significantly (36% to <6 %) and at the end of the trial Tiichostrongylus larvae predominanted in larval cultures (>80%) . Mineral analysis revealed deficiencies in sodium and copper, low levels of zinc and normal levels of potassium, calcium, magnesium and phosphorus . Wormolas had a significant effect on sodium and zinc status but not on copper although sufficient levels of this element were available. Comparison of bodyweight gains showed a significantly (P<0.05) higher rate of increase in the treated animals.